Die Entwicklung des Partnermarkts im Längsschnitt - Alters- und Kohortenunterschiede - Eckhard, Jan; Stauder, Johannes; Wiese, Daniel (Social Demography Forschung an der Schnittstelle von Soziologie und Demografie, 2016)
For the first time, this study provides longitudinal research on regional partner market conditions and trends in Germany. It works with indicators of the partner market that are appropriate to theoretical concepts. Using ministerial regional population data, the study examines several assumptions about how the partner market alternates over the life course and differs between birth cohorts. It describes differences between partner market conditions of the sexes and shows effects on the partner market that derive from changes of the birth rate, from shifts in the prevalence and forms of couple relationships, from the expansion of higher education, and from migration.